2017
DOI: 10.1002/jbio.201600284
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive diagnostic system and its opto‐mechanical probe for combining confocal Raman spectroscopy and optical coherence tomography

Abstract: Non-invasive optical diagnostic methods allow important information about studied systems to be obtained in a non-destructive way. Complete diagnosis requires information about the chemical composition as well as the morphological structure of a sample. We report on the development of an opto-mechanical probe that combines Raman spectroscopy (RS) and optical coherence tomography (OCT), two methods that provide all the crucial information needed for a non-invasive diagnosis. The aim of this paper is to introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Results showed that distinct epithelial and stromal tissue layers could be rapidly visualized with OCT imaging, and CRS could then be used to interrogate specific Raman spectral signatures from these layers to isolate their depth-dependent signals. Transitioning into fiber-based CRS, an important step toward system portability, Maher et al [83] and Klemes et al [79] each reported a collection geometry where the RS collection fiber was positioned at a conjugate image plane to act as a pinhole and achieve confocal detection. Ren et al most recently demonstrated fiber confocal detection [84], which expanded the confocal capabilities of a CRS-OCT system by including a tunable lens in the RS laser path to position the Raman probing beam at any arbitrary transverse and axial position within the OCT volumetric image.…”
Section: Axially Selective Rs-octmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that distinct epithelial and stromal tissue layers could be rapidly visualized with OCT imaging, and CRS could then be used to interrogate specific Raman spectral signatures from these layers to isolate their depth-dependent signals. Transitioning into fiber-based CRS, an important step toward system portability, Maher et al [83] and Klemes et al [79] each reported a collection geometry where the RS collection fiber was positioned at a conjugate image plane to act as a pinhole and achieve confocal detection. Ren et al most recently demonstrated fiber confocal detection [84], which expanded the confocal capabilities of a CRS-OCT system by including a tunable lens in the RS laser path to position the Raman probing beam at any arbitrary transverse and axial position within the OCT volumetric image.…”
Section: Axially Selective Rs-octmentioning
confidence: 99%
“…This micro‐optical design facilitated miniaturization of the RS‐OCT probe so that it could fit within the oral cavity. In another study, Klemes et al reported a RS–OCT probe with a length of 165 mm that consisted of separate RS and OCT fiber‐coupled paths housed in a common miniature scanning head (Figure 5B) [79]. This was attached to an automated scanning system so that user‐selected positions within an OCT scan could then be targeted for RS acquisition through software control of the motorized stage.…”
Section: Multimodal Rs–oct: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectroscopy has different applications in biomedical fields, but it is mostly used in diagnostics [6] and therapy [7]. The use of visible spectroscopy for hematic analysis is however a promising approach, because absorbance spectra of blood contain a lot of information such as hematocrit, oxygen saturation, but also platelets [8] and glucose [9] concentrations, allowing the possibility to significantly increase the amount of parameters to be monitored.…”
Section: Introductionmentioning
confidence: 99%
“…It is highly desirable to combine the RS and OCT techniques for simultaneously acquiring both tissue morphology and biochemical information on the same tissue in real‐time. Previous studies on the combined RS and OCT are largely limited to the bench‐top optics , and the 2 optical techniques are conducted sequentially with lengthy acquisition time , unsuited for rapid in vivo tissue measurements in clinical settings. Since the biochemical and morphological profiles of distinctive anatomical regions in the oral cavity can be highly functionally specialized and exhibit significant variations in architectural properties and cell types (eg, tissue thickness, distinct epithelium types, vascularity, papillae, bone, etc.)…”
Section: Introductionmentioning
confidence: 99%